Construcciones en bahareque en los municipios de Circasia y Calarca georreferenciados (2017)
"This investigative work arises from the hypothesis ""implementation of the geographic information system in the training of technologist complemented with the constructions in the technique of the bahareque"", likewise will be associated with the constructions in bahareque of the municipalities of Calarcá and Circasia within the framework of cultural heritage. Currently there is no document or any development that alludes to the georeferencing of the constructions in the vernacular system bahareque, starting from the generation of a map with intervention of the system ARCMAP, in order to make known its type of bahareque, constructive process, among other information extracted from the center page Grancolombiano Cultural Landscape coffee.What this research is looking for is to generate a product that will be the georeferenced map and will give a specialization of the properties built in this technique so that we can conclude that most of the constructions in the municipalities of Calarcá and Circasia at the moment To make the due process of georeferencing the totality of the properties is identified that the majorityof the constructions in these municipalities are of type bahareque cemented, inlay ""Earth"", It also gives the implementation of different types of adobe but are very scarce in these municipalities. In order to imply that in the training of technologist the geographic Information system can also be used for academic purposes"